Effectiveness of Using MIT App Inventor as an Android-Based Learning Media - Miftahul Jannah; Khairunnisa Khairunnisa; Teguh Ansyor Lorosae; Sahrul Ramadhan (LPPM Universitas Islam 45 Bekasi, 2023)
Massive updates on technology make teachers have to be more extra in determining the learning materials and media used. The technology used must be up-to-date and provide good results as a learning medium that must be used. Technological developments must truly be transferable as learning media, given that Revolution 5.0 is targeting innovation and development in more sophisticated technologies such as AI, IoT, and robots. Humans can slowly be replaced with machines and everything may be computerized. By being given knowledge from now on, at least students have provisions for the future. The process of transferring knowledge is not only done by speaking in front of the class, the process also requires media or intermediaries to bridge it so that the process of transferring knowledge becomes more optimal and faster. The use of appropriate learning media can certainly make students better understand what is being taught. On this basis, the purpose of this study was to determine the effectiveness of using Mit App Inventor as a learning medium. The method used is Descriptive Quantitative. Data collection was carried out by distributing questionnaires to students of SMK 1 Muhammadiyah Bima who had used Mit App Inventor in their learning process. The results of this study indicate that the use of Mit App Inventor at SMK 1 Muhammadiyah Bima is effective. The first indicator